1999
DOI: 10.1080/07315724.1999.10718892
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of Vitamin C, Vegetables and Fruits: Which Schoolchildren Are at Risk?

Abstract: A considerable number of children drastically under-consumed vitamin C and total vegetables and fruits. Overall, children with desirable vitamin C intakes had healthier diets, including more milk and vegetables, than did their peers with low vitamin C intakes. Health care professionals should continue to promote at least five daily servings of vegetables and fruits and should advise parents that at least one of these should be rich in vitamin C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…However, it is widely known that individuals do not consume isolated foods/nutrients but meals that consist of a combination of foods and nutrients. Therefore, although several epidemiological studies have revealed increased consumption of energy, inadequate intake of certain nutrients (that is, fiber), excessive intake of other nutrients (that is, total fat, saturated fat, sugar) and low consumption of fruits and vegetables among children, it does not reflect the overall diet quality (Hampl et al, 1999;Ballew et al, 2000;Kranz et al, 2004Kranz et al, , 2005aManios et al, 2008). As a result, dietary pattern analysis has recently emerged as an alternative approach to evaluate diet quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is widely known that individuals do not consume isolated foods/nutrients but meals that consist of a combination of foods and nutrients. Therefore, although several epidemiological studies have revealed increased consumption of energy, inadequate intake of certain nutrients (that is, fiber), excessive intake of other nutrients (that is, total fat, saturated fat, sugar) and low consumption of fruits and vegetables among children, it does not reflect the overall diet quality (Hampl et al, 1999;Ballew et al, 2000;Kranz et al, 2004Kranz et al, , 2005aManios et al, 2008). As a result, dietary pattern analysis has recently emerged as an alternative approach to evaluate diet quality.…”
Section: Introductionmentioning
confidence: 99%
“…Children's 'poor' diet observed in developed countries during last decades have resulted in an increasing prevalence of risk factors for chronic diseases such as obesity, high blood pressure and increased cholesterol levels in children (Hampl et al, 1999;Devaney et al, 2004;Kranz et al, 2004;Muntner et al, 2004;Angelopoulos et al, 2006;Magkos et al, 2006;Manios et al, 2008). Both the aforementioned clinical risk factors and several behavioral factors, such as unhealthy dietary habits or lifestyle patterns, originating in early life seem to track into adulthood increasing the risk for developing chronic diseases in adult life (Boulton et al, 1995;Hesketh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…)'; (3) 'Do you think this product is healthy?' The questions about the advertisements asked participants whether they thought the advertisement's message was that the product was: (1) Nutritionally beneficial; (2) Healthy; (3) Tasty; (4) Fun; (5) Exciting and new; (6) Something that would make one popular; and (7) Convenient. All questions had a 'yes' or 'no' response format.…”
Section: Methodsmentioning
confidence: 99%
“…Overweight children are far more likely to become obese as adults 5 . Research shows that the majority of children consume insufficient amounts of fruit, vegetables, dietary fibre 6 , and milk and meat products; and consume higher than recommended amounts of calorie-dense and high-fat foods 7,8 . A variety of factors have been reported to influence food choice, including physiological, psychological 9 , social 10 , environmental 11 and cultural factors 12 .…”
mentioning
confidence: 99%
“…96 Hampl et al, 97 conducted a survey on diet of school children and concluded that children consuming higher fruits and vegetables had higher level of VC and were more healthy. In 2004 Hung et al 98 stated that higher consumption of fruits and vegetables was associated with a comparable decrease in major chronic disease risk and further supported the recommendation of consuming five or more servings of fruits and vegetables daily.…”
Section: Sourcesmentioning
confidence: 99%